2009
DOI: 10.2460/javma.234.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical and magnetic resonance imaging findings with outcome in dogs with presumptive acute noncompressive nucleus pulposus extrusion: 42 cases (2000–2007)

Abstract: Clinical and MRI findings can help predict outcome in dogs with acute noncompressive nucleus pulposus extrusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
255
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(286 citation statements)
references
References 36 publications
25
255
2
4
Order By: Relevance
“…[4][5][6]8 Because it is rare to definitively diagnose either condition prior to the death of the patient, both conditions are presumptively diagnosed on the basis of the presence of characteristic clinical findings in conjunction with established MRI criteria. [1][2][3][7][8][9] Although investigators of previous studies 1,2,5,8,10 have reported the characteristic clinical and diagnostic features of ischemic myelopathy and ANNPE separately, to our knowledge, no studies have been performed to compare the clinical signs and outcomes between ischemic myelopathy and ANNPE. Identification of any differences in the clinical findings and outcomes for these 2 conditions could be clinically relevant for attaining a presumptive antemortem diagnosis and developing both short-and long-term prognoses.…”
Section: Small Animals and Exoticmentioning
confidence: 87%
See 4 more Smart Citations
“…[4][5][6]8 Because it is rare to definitively diagnose either condition prior to the death of the patient, both conditions are presumptively diagnosed on the basis of the presence of characteristic clinical findings in conjunction with established MRI criteria. [1][2][3][7][8][9] Although investigators of previous studies 1,2,5,8,10 have reported the characteristic clinical and diagnostic features of ischemic myelopathy and ANNPE separately, to our knowledge, no studies have been performed to compare the clinical signs and outcomes between ischemic myelopathy and ANNPE. Identification of any differences in the clinical findings and outcomes for these 2 conditions could be clinically relevant for attaining a presumptive antemortem diagnosis and developing both short-and long-term prognoses.…”
Section: Small Animals and Exoticmentioning
confidence: 87%
“…2,8,14,15 Regardless of the condition (ischemic myelopathy or ANNPE), the clinical status of affected dogs typically stabilizes or improves within 24 hours after the onset of neurologic signs without specific treatment. [2][3][4]10 The long-term outcome for both conditions is generally favorable, although the outcome is less favorable for dogs that lose nociception in affected limbs, develop symmetric neurologic deficits, have a lesion affecting the spinal cord intumescences, or have specific MRI findings such as a lesion affecting a large area of the spinal cord. [2][3][4][5] ABBREVIATIONS ANNPE Acute noncompressive nucleus pulposus extrusion CI Confidence interval QOL Quality of life SCS Spinal cord segment…”
Section: Comparison Of Clinical Signs and Outcomes Between Dogs With mentioning
confidence: 99%
See 3 more Smart Citations